Investigating the Effect of Acupuncture on Facilitating Placenta and Fetus Removal in Difficult Labors - Kolookhi, Yousef; Modoodi, Mozhgan; Ataei , Mina; Rezapour-Nasrabad , Rafat; Bazrafkan, Mahshid; Tourzani, Zahra Mehdizadeh; Mirzaei, Maryam; Hagpanah, Gohar (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: Due to the side effects of the pharmacological methods, there is a greater tendency to use non-pharmacological methods, such as acupuncture. The objective of the present study is to investigate the effect of acupuncture on facilitation of placenta and fetus removal during difficult labors. Materials and Methods: This single-blind randomized clinical trial was conducted on 60 mothers referred to maternity hospitals of Shahroud. The mothers were divided into two groups (each group included 30 mothers). The placenta and fetus were removed in the control group (control) with no intervention and normally. The times of placenta and fetus removal and postpartum pain and the studied factors were recorded. The placenta and fetus were removed in the second group (experimental group) with intervention of acupuncture since the beginning of the contractions and pain, and all stages were recorded. The data were analyzed through SPSS software. Results: The results showed that the duration and level of pain in the first stage of labor and the need for labor augmentation with oxytocin in the acupuncture group were significantly less than those of the control group. Conclusion: It can be concluded that acupuncture reduces the duration of labor, reduces the need for oxytocin, and reduces the level of pain in the first stage of labor. Therefore, it is recommended to encourage the mothers to have a normal vaginal delivery via acupuncture to improve the process of normal vaginal delivery and further promote the natural vaginal delivery in the community.